Perubahan morfologi larva nyamuk akibat pemberian larvasida bakteri kitinolitik - Yekki Yasmin; Lenni Fitri (Perhimpunan Entomologi Indonesia, 2013)
The aim of this research is to evaluate the change of Aedes aegypti L. and Culex spp. larvae morphology effected by chitinolitic bacteria as larvacide. This research was conducted in Microbiology Laboratory, Faculty of Math and Natural Science, University of Syiah Kuala. The sample was taken from several areas in Banda Aceh and Aceh Besar. The isolation was accomplished by plating 1 ml of sample water on chitin agar medium and incubating for 48–72 hours in 30 °C temperature. In the experimental method, three concentrations of chitinolitic bacteria (0.5, 1.0, and 1.5 ml) in 7 days observation were used as a treatment. The research resulted in 6 isolates having the potential to be developed firther as chitinolitic bacteria. The result shows that chitinolitic bacteria degrades exosceleton of second instar larvae of Aedes aegypti and Culex spp. Degradation of exoskeleton started on the 4th days and occurred at the thorax region. All exoskeleton from both species are completely broken on day six.